Morphological and Molecular Characteristics of Alternaria citrus stem end rot - Kareem, T. A.; Jamel, Dareen S.; Ali, Abdulzahra Jabar; Saeed, R. I. (International Journal of Psychosocial Rehabilitation, 2020)
Citrus stem end rot symptoms on citrus fruit were observed in Alsuwaira orchard citrus since 2015 in Wasit province, Iraq. Infected citrus fruits were collected to isolate and characterize the pathogenic factors. The isolates showed that Alternaria spp. has been involved in infected citrus fruit. Genetic characteristics were analyzed based on sequence of rDNA-internal transcribed spacer (ITS) region. The phylogenetic tree based on rDNA- ITS analysis showed that the Alternaria alternata the main pathogenic factor of citrus stem end rot.Molecular identity of rDNA-ITS region of the present isolates were deposited in the GenBank database under the eight accession numbers from MK121457 to MK121464.